Justiciabilidade das violações de direitos fundamentais das pessoas privadas de liberdade (uma aproximação Brasil e EUA) - Oliveira, Rodrigo Moraes de (2015)
Daily violations of fundamental rights of persons deprived of liberty in Brazil, emulated by a grotesque scenario of overcrowding in prisons, in spite of a solid legal framework founder of protections, associated with paralysis of successive governments and the parliament, leading to the question about whether they would be justiciable. Being clear that there is a special subjection relationship of the prisoner in the face of the State, which figure as your guarantor, and that the Constitution will be to govern the hand of the judge, the affirmation of justiciability comes naturally. Touches him checking not only the existence of formal condition to prison (i.e., a valid incarceration title), but, overcoming the traditional look, also the existence of material conditions to prison (i.e., humanitarian practicability of imprisonment, in loco, in the prison unit - in accordance with fundamental rights). In the US, the Supreme Court issued a paradigmatic judgment in the area, in Brown vs. Plata (2011), ordering the release of prisoners in California due to overcrowding and inherent violations. In Brazil, the ADPF in the collective via, and the HC in the individual via, are possible actions to search tutelage. Among the resulting statements which can not invade the sphere of action of the elected branches of government, under penalty of improper judicial activism, the temporary suspension of imprisonment is an alternative limit, also in view of the principle of unsurpassable prison capacity.